2013
DOI: 10.19026/ajfst.5.3093
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Chemical Changes of Nile Tilapia (<em>Oreochromis niloticus</em> L.) Fillet during Ice Storage: Effect of Age and Sex

Abstract: Fish is one of the most highly perishable food products. The aim of this study was to investigate microbiological and chemical changes of Nile tilapia fillet during ice storage. Nile tilapia samples were collected from Lake Zeway, Ethiopia. The fillet was stored at 0°C for 30 days on ice. Total plate count, total and fecal coliform, total volatile base nitrogen and pH was measured at the interval of four days. Regardless of age and sex, Total plate count varied between 4 to 11.74 log cfu/g. Total coliform coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
(12 reference statements)
3
10
1
1
Order By: Relevance
“…For this reason, higher pH coupled with higher microbial counts increases with longer holding and storage time, that is, with increased spoilage. A similar trend has been reported in previous shelf‐life studies on fish products (Magnusson and others , ; Okeyo and others ; Susanto and others ; Lema Abelti ). Likewise, the slower increase in pH in the fillets packed immediately after processing was explained by delays in bacterial growth and spoilage.…”
Section: Resultssupporting
confidence: 89%
“…For this reason, higher pH coupled with higher microbial counts increases with longer holding and storage time, that is, with increased spoilage. A similar trend has been reported in previous shelf‐life studies on fish products (Magnusson and others , ; Okeyo and others ; Susanto and others ; Lema Abelti ). Likewise, the slower increase in pH in the fillets packed immediately after processing was explained by delays in bacterial growth and spoilage.…”
Section: Resultssupporting
confidence: 89%
“…The present results are not in accordance with those obtained by Abelti (2013) who reported that bacterial count was ranged from 6.33 CFU/g on day zero and 11.74 CFU/g on day 26 of storage in ice.…”
Section: Sensory Evaluation Of Grey Mulletcontrasting
confidence: 99%
“…Finally the number of colonies were counted and multiplied by dilution factor to calculate the total colonies forming units per g sample (Abelti, 2013).…”
Section: Materials:-mentioning
confidence: 99%
“…The total volatile basic nitrogen (TVB-N) value was estimated by the micro-diffusion method (Abelti, 2013) following the distillation of the perchloric acid of the homogenized fish samples. The distillate was collected in a flask containing aqueous solution of boric acid and methyl red as an indicator.…”
Section: Total Volatile Basic Nitrogenmentioning
confidence: 99%